LAND CARRYING CAPACITY STATUS BASED ON ECOLOGICAL FOOTPRINT IN PENEBEL DISTRICT, TABANAN REGENCY, BALI - Sudipa, Nyoman; Yastika, Putu Edi; Widiantara, I Kadek (LPPM Universitas Jambi, 2026)
Land carrying capacity is influenced by population, and land availability is assumed to be equivalent to the price of rice by using all food potential in a region. As one of Bali's rice granaries, Penebel Regency plays an important role in providing food for the Balinese people. This study aims to assess the condition of agricultural land area, determine agricultural land availability, estimate food needs based on population, and analyze the status of agricultural land carrying capacity by comparing land availability and land needs, as well as the status of land carrying capacity based on the ecological footprint. The research method uses a quantitative approach, drawing on primary data from direct field observations, survey databases, and field interviews, and secondary data from previous research and government reports. Data analysis uses calculations of land capability, land availability, and land carrying capacity based on the ecological footprint. The results of the study indicate that the land requirements and availability in Penebel Regency total 15,615.84 hectares. Land requirements based on the ecological footprint are 4,420 hectares, while land availability in Penebel Regency is 15,615.84 hectares. This indicates that the land carrying capacity in Penebel Regency can still accommodate the population's food needs, with a surplus of 11,195.84 hectares. The renewal in this study lies in the surplus land-carrying capacity from an ecological footprint perspective, amid the siege of modernism and the community’s continued maintenance of agriculture as part of its agrarian culture.